Peran New Service Development Dalam Inovasi Layanan Perpajakan Melalui Pengembangan Aplikasi Coretax Oleh KPP Pratama Bandung Cicadas - Amalia Fauziah Rahmah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the role of New Service Development (NSD) in tax service innovation through a case study of the development of the Coretax application at KPP Pratama Bandung Cicadas. The research method used is a descriptive qualitative approach with an in-depth interview approach to stakeholders at KPP Pratama Bandung Cicadas. The results of the study indicate that the development of the Coretax application plays a significant role in increasing the efficiency and transparency of public services in the taxation sector. This application not only simplifies the core business processes of tax administration, from taxpayer registration, SPT reporting, tax payments, to tax audits and collection. But also, it allows for better supervision of tax activities. In the context of NSD, this innovation illustrates how technology-based service updates can drive modernization and meet the increasingly complex needs of society. The positive impact of this innovation is seen in the ease and efficiency for taxpayers. Through one integrated system, taxpayers can access and manage all tax administration services practically.